Sweet 16 to life - Kim Reid (: Kensington Publishing Corp., 2013)
Using skills from her police officer mother to expose deception at her exclusive private school, Chanti risks her freedom and reputation to protect a friend from a vengeful gang member while mending fences with an ex-boyfriend.